2018
DOI: 10.31195/ejejfs.435962
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on the potential distribution of Taxus baccata L. in the Eastern Mediterranean and the Bolkar Mountains (Turkey) from Last Glacial Maximum to the future

Abstract: The Pleistocene is an important period for assessing the effects of climate change on biological diversity. In the beginning of this period, many tree species disappeared in the flora of Europe, with ongoing, but smaller losses later, and many tree species exhibiting repeated strong range shifts mostly at the end of the period. It is thought that some areas will be more affected from possible climate change. The Mediterranean Basin is the most important among the mentioned sensitive areas. Species with scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This demonstrates that climate change not only result in habitat losses, but they also affect many variables in the ecosystem. Other similar studies have supported this situation (Süel et al, 2018;Koç et al, 2018;Mert and Kıraç, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…This demonstrates that climate change not only result in habitat losses, but they also affect many variables in the ecosystem. Other similar studies have supported this situation (Süel et al, 2018;Koç et al, 2018;Mert and Kıraç, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…The results show that the distribution areas of all three Tilia species will change due to climate change and the loss area will be 43,5 km 2 (4%) for T. tomentosa, 9.953,6 km 2 (15%) for T. platyphyllos and 448 km 2 (19%) for T. cordata. Koç et al (2018) showed that Taxus baccata will find suitable conditions in the Bolkar Mountains region, pointing it out as an important refuge. They also found that the distribution of 2020) stated that Fagus orientalis will face a dramatic range narrowing in the future and will prefer the mountainous regions of the Caucasus for its distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Pindrow and T. baccata are more vulnerable to climate changes (Thapa et al 2013, Yousaf et al 2022. These two species in this temperate forest are dominant (Muhammad et al 2021), having rapid growth and according to recent studies these species have potential sensitivity for dendroclimatological studies (Thapa et al 2013, Shaheen et al 2015, Koc et al 2018, Ullah et al 2022. However, little is known on the relationship between climate and growth for these two species in the study site, we explored this correlation with regional temperature and precipitation variability to assess their potential for climate reconstruction.…”
Section: Introductionmentioning
confidence: 98%